2015
DOI: 10.1002/jcb.25390
|View full text |Cite
|
Sign up to set email alerts
|

The P2RY2 Receptor Induces Carcinoma Cell Migration and EMT Through Cross‐Talk With Epidermal Growth Factor Receptor

Abstract: Extracellular nucleotides are signaling elements present in the tumor microenvironment; however, their role in tumor growth is not completely understood. In the present study, we asked whether nucleotides regulate cell migration in ovarian carcinoma-derived cells. We observed that 100 μM UTP induced migration in SKOV-3 cells (1.57 ± 0.08 fold over basal), and RT-PCR showed expression of transcripts for the P2RY2 and P2RY4 receptors. Knockdown of P2RY2 expression in SKOV-3 cells (P2RY2-KD) abolished the UTP-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 48 publications
(67 reference statements)
2
39
0
Order By: Relevance
“…In previous studies, we demonstrated that SKOV‐3 cells release ATP into the extracellular medium [Vázquez‐Cuevas et al, ]. In addition, we showed that the incubation of SKOV‐3 cell cultures with apyrase induced a relocation of E‐cadherin from the cytosol to the cellular junctions [Martínez‐Ramírez et al, ].…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…In previous studies, we demonstrated that SKOV‐3 cells release ATP into the extracellular medium [Vázquez‐Cuevas et al, ]. In addition, we showed that the incubation of SKOV‐3 cell cultures with apyrase induced a relocation of E‐cadherin from the cytosol to the cellular junctions [Martínez‐Ramírez et al, ].…”
Section: Resultsmentioning
confidence: 85%
“…In previous studies on ovarian carcinoma‐derived SKOV‐3 cells, we observed that purinergic signaling is able to mediate the induction of epithelium to mesenchymal transition (EMT). These cells release ATP into the extracellular space, and the addition of apyrase to the culture medium favored the epithelial phenotype, as evidenced by the location of E‐cadherin in the cellular contact zone [Martínez‐Ramírez et al, ]. Our observations led us to hypothesize that there was a balance between ATP released in SKOV‐3 cells and its catabolites, produced by ectonucleotidase activity and resulting purinergic receptor responses.…”
mentioning
confidence: 84%
“…Interestingly, treatment with apyrase, an ectonucleotidase that cleaves ATP to ADP and AMP, reduced basal migration and favored the epithelial phenotype. This action promoted a relocation of E-cadherin to cellular junctions, strongly suggesting that dephosphorylated metabolites of ATP participate in the control of EMT induction [89]. The increment in invasiveness, together with the downregulation of epithelial markers and the expression of mesenchymal markers mediated by the P2Y2 receptor, was also demonstrated in a highly metastatic breast cancer cellular line named MDA-MB-231, through a pathway mediated by PKC activity [90].…”
Section: Purinergic Signaling Emt and Invasivenessmentioning
confidence: 87%
“…A total of 1000 ng normalized RNA samples were reverse transcribed using a RevertAid™ H Minus first strand cDNA synthesis kit (Thermo Fisher Scientific). The integrity of the cDNA was assured by PCR with GAPDH specific primers targeting 496 bp sequence in the GAPDH cDNA (Table ); the reaction constituted 1 μL cDNA, 1× Taq buffer, 1 U Taq polymerase, 1.5 mM MgCl 2 , 0.4 mM dNTPs, 0.4 μM each primers; thermal conditions (i) 94°C for 3 min (initial denaturation) (ii) 35 cycles at 94°C for 1 min, 58°C for 1 min, 72°C for 1 min (iii) final extension (72°C for 10 min) . Relative quantitative PCR was performed on Stratagene Mx3005p real‐time PCR cycler (Agilent) using SYBR green dye chemistry.…”
Section: Methodsmentioning
confidence: 99%